HUBUNGAN ANTARA HIPERURISEMIA DENGAN KEJADIAN HIPERTENSI PADA LANSIA DI UPT PELAYANAN SOSIAL TRESNA WERDHA (PSTW) BONDOWOSO - Faridha Puspitasari; Marwah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2018)
The increasing number of elderly causes problems, especially in terms of health and well-being of the elderly. The existence of the disease affects the condition of one's physical health which is one aspect that determines the quality of one's life. The disease that often affects the elderly is hyperuricemia and hypertension. The purpose of this study is to determine the close relationship between hyperuricemia and the incidence of hypertension in the elderly. The research design used was Observational Analytic with cross sectional approach. The sample amounted to 58 with sampling using random sampling techniques. Data collection method uses uris acid meter and sphygmomanometer then data is analyzed using Chi Square statistical test with Contingency Coefficient. The results of the analysis are the majority of respondents who have hyperuricemia with hypertension (73%), who have hyperuricemia but do not have hypertension (27%), who do not have hyperuricemia but have hypertension (23.8%), and who do not experience hyperuricemia and do not experience hypertension as much (76.2%) The results of the analysis of the two veriabels obtained p value = 0.001, cc = 0.529, and OR = 8.640. The conclusion in this study is that there is a fairly close relationship between hyperuricemia with the incidence of hypertension in the elderly at UPT PSTW Bondowoso. Suggestions for health workers should increase the intensity of providing health education to the elderly through counseling, as well as checking for uric acid and blood pressure regularly